2020
DOI: 10.3390/su12083129
|View full text |Cite
|
Sign up to set email alerts
|

Affordable Housing vs. Urban Land Rent in Widespread Settlement Areas

Abstract: Social housing constitutes a partial response to the demand for affordable housing. In Europe, there are different forms of social housing, which are distinguishable based on whether they employ a universal or residual approach. The latter is employed by Italian initiatives for social residential construction, the financial instrument of which is the Investment Fund for Housing, a closed-end fund managed by CDP (Cassa Depositi e Prestiti) Investment, which provides public–private partnerships. The main obstacl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…In this context, it is clear that the level of taxation is the only certain element among those that contribute to the formation of the return-at any rate, in the short term. This is a factor that could (even with small oscillations) act as a flywheel or a curb for the demand for real estate, which is undoubtedly true for the part that contains the prevailing economic component by virtue of the strong elasticity that it shows in proximity to an expected rate of return close to the rate of alternative investments [20].…”
Section: Real Estate Market and Taxationmentioning
confidence: 99%
“…In this context, it is clear that the level of taxation is the only certain element among those that contribute to the formation of the return-at any rate, in the short term. This is a factor that could (even with small oscillations) act as a flywheel or a curb for the demand for real estate, which is undoubtedly true for the part that contains the prevailing economic component by virtue of the strong elasticity that it shows in proximity to an expected rate of return close to the rate of alternative investments [20].…”
Section: Real Estate Market and Taxationmentioning
confidence: 99%
“…Approximately 1.26 billion people in emerging nations are estimated to live in inadequate housing, and this number will rise to 3 billion people by 2030 (156). Among the approaches to model access to housing or shelter, demographic variables, such as household formation, or economic variables, including aspects of housing markets and affordability, are typically considered important drivers of changes in housing stocks and flows over time (157)(158)(159). Recent studies (160) showed that provision of durable housing for all could result in considerable energy footprints, even if the increase in energy provision for basic decent living does not pose, in itself, a threat to climate change mitigation (160).…”
Section: Modeling Decent Living Standardsmentioning
confidence: 99%
“…Moreover, many countries in the region, including Ethiopia, lack comprehensive policies on land acquisition for housing, leading to unclear legal frameworks and a lack of transparency in the land acquisition process (Toulmin, 2009;UN-Habitat, 2011;Arjjumend and Seid, 2018;Lamson-Hall et al, 2019;Larsen et al, 2019). Another significant factor is the high cost of land in urban areas resulting from the alarmingly high demand of serviced land for housing and its limited supply (Berto et al, 2020;Yimam et al, 2022). Hence, land prices have skyrocketed in recent years, making it increasingly difficult for developers to acquire land for affordable housing (UN-Habitat, 2011;Yimam et al, 2022).…”
Section: Introductionmentioning
confidence: 99%